Biogeografia de restingas: padrões e determinantes da variação florística no litoral brasileiro - Silva, Karla Juliete de Paiva (2016)
Aim The plant communities of restinga are shaped by species from Caatinga, Cerrado, Amazon and Atlantic Domains which are able to cope with stressful conditions from the Brazilian coast. We tested whether environmental variation along the Brazilian coast is strong enough to impose additional filters for the restinga species. Location The entire coast of the Brazil, South America. Methods We gathered information about species composition from 164 distinct localities along the Brazilian coast to construct a binary database of restinga flora. For each of these localities, we obtained a set of 41 environmental variables, including climate and edaphic variables. We used Species Archetype Models (SAMs) to evaluate the response of the restinga species to the variation represented by abiotic variables. We also investigated the existence of floristic gradients using a Principal Coordinates Analysis (PCoA). We use these two statistical approaches for data of herbaceous and woody species, separately. Results We found four archetypes of herbaceous species in response to 10 environmental variables, and 10 archetypes of woody species in response to 6 environmental variables. The archetypes of herbaceous responded to environmental gradients more strongly than archetypes of woody species, althout, in general, just few archetypes showed strong responses to environmental variation. Additionally, the herbaceous communities from restinga were not structured by significant floristic gradients and the woody communities did not have clear floristic gradientes, suggesting a high level of stochasticity shapping the floristic structure of restinga. Main conclusions The environmental variation along the Brazilian coast seems to create additional filters for herbaceous and woody species of restinga, which are more important to the distribution of herbaceous species. However the low response of species to the environment suggests that the floristic variation of restinga results over from a spatial relationship between the restinga and the Caatinga, Cerrado, Amazon, Atlantic and Pampa Domains.